2010
DOI: 10.1158/1940-6207.capr-09-0116
|View full text |Cite
|
Sign up to set email alerts
|

American Ginseng Suppresses Colitis through p53-Mediated Apoptosis of Inflammatory Cells

Abstract: Ulcerative colitis is a dynamic, chronic inflammatory condition associated with an increased colon cancer risk. Inflammatory cell apoptosis is a key mechanism regulating ulcerative colitis. American ginseng (AG) is a putative antioxidant that can suppress hyperactive immune cells. We have recently shown that AG can prevent and treat mouse colitis. Because p53 levels are elevated in inflammatory cells in both mouse and human colitis, we tested the hypothesis that AG protects from colitis by driving inflammatory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 49 publications
4
70
0
1
Order By: Relevance
“…China NGP has become a commercial product for patients with various kinds of infections to improve the immune defense during infections, immune dysfunction and other immune boosting needed situation, such as cancers. [8][9][10][11][12] However, so far there are no reports on either the concrete mechanisms or maturation changes of DCs post treatment with NGP and the precise mechanisms to regulate the cells in immune system through dendritic cells (DCs) by NGP remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…China NGP has become a commercial product for patients with various kinds of infections to improve the immune defense during infections, immune dysfunction and other immune boosting needed situation, such as cancers. [8][9][10][11][12] However, so far there are no reports on either the concrete mechanisms or maturation changes of DCs post treatment with NGP and the precise mechanisms to regulate the cells in immune system through dendritic cells (DCs) by NGP remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A dysfunctional intestinal immune system is a major mechanism by which chronic inflammation occurs in ulcerative colitis and defects in apoptosis of mucosal inflammatory cells is critical in the pathogenesis of ulcerative colitis. Another study conducted by Jin et al (149), showed that AG extract can drive apoptosis of inflammatory cells through the p53 mechanism in vitro which is consistent with dietary AG protecting against DSS-induced colitis in the mouse model.…”
Section: American Ginsengmentioning
confidence: 54%
“…Paraffin embedded tissues were serially sectioned, and one section from each mouse was stained with H&E. Sections were microscopically examined for histopathologic changes, as we did previously (Jin et al, 2010).…”
Section: Methodsmentioning
confidence: 99%